Integrasi Prinsip Universal Design for Learning (UDL) Pada E-Modul Matematika Berbasis Problem-Based Learning Di Kelas VII SMP - Bertu Rianto Takaendengan; Agusyarif Rezka Nuha; Taulia Damayanti; Patra Lasantu; Adib Rizal Kundju (Jambura Journal of Mathematics Education, 2025)
The development of digital technology requires innovative teaching materials that are interactive, adaptive, and inclusive, particularly in mathematics learning, which is still dominated by conventional methods and results in low student achievement. This study aimed to develop a mathematics e-module based on Problem-Based Learning (PBL) with the integration of Universal Design for Learning (UDL) principles on ratio material for seventh-grade students. The research was conducted at SMP Negeri 1 Wonosari during the even semester of the 2024/2025 academic year using the research and development approach with the 4D model (define, design, develop, disseminate), involving experts for validation as well as teachers and students for trials. Data were collected through validation sheets, questionnaires, and learning achievement tests, and analyzed descriptively. The results showed that the developed e-module met the feasibility criteria with an average of 86.75% (Good category) and was rated very practical with a score of 88% by teachers and students. The limitation of this study lies in its narrow scope; therefore, further research is recommended to involve broader materials and diverse school contexts. This study confirms that the integration of PBL and UDL in e-modules can serve as an innovative alternative to support mathematics learning that is more interactive, contextual, and inclusive.